The Role of the Honorary Tribunal of the Notary of the Territory at the Request of Law Enforcement Against Alleged Violations by the Notary - Eli Erlina (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2022)
The Honorary Panel of Notaries rejected the investigator's application for approval in the judicial process. The rejection of the case was carried out by testing article 66 of Law Number 2 of 2014 concerning the Position of Notary at the Constitutional Court. This study aims to analyze the role of the Regional Notary Honorary Assembly at the request of law enforcement against alleged violations by notaries, and to analyze the reasons for the refusal of the Regional Notary Honorary Assembly to the application for examination of the Notary by police investigators. The approach method used in this study is normative juridical which is prescriptive. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The results of this study show that: The role of the Regional Notary Honorary Council in responding to the request of the investigator to present as a witness or suspect in the case that is resolved, the Regional Notary Honorary Council can refuse and or grant the request, very much depends on the objective conditions at the time of the examination of the notary. The reason for the Regional Notary Honorary Council refusal to the investigator's request to present a Notary as a witness or suspect, if from the results of the hearing the examination of the object in the Deed before the Deed was made was carried out in accordance with the standard operating procedures according to theKeyword: the Regional Notary Honorary Council; Law Enforcement; Offense Notary